Preparation of minor ginsenosides C-Mx and C-K from notoginseng leaf ginsenosides by a special ginsenosidase type-I. Issue 12 (December 2015) - Liu, Chunying; Zuo, Kangze; Yu, Hongshan; Sun, Changkai; Zhang, Tianyang; Xu, Longquan; Jin, Yinghua; Im, Wan-Teak; Jin, Fengxie
Graphical abstract: Highlights: C-Mx and C-K were produced from notoginseng leaf ginsenoside by ginsenosidase type-I enzyme. Enzyme of Aspergillus niger g.848 first hydrolyzes 20- O -Glc of Rb1, and then 3- O -Glc of Rb2 and Rc. Enzyme mainly hydrolyzed 3- O -Glc of Rb3 to C-Mx1 → C-Mx → C-K. The rate of hydrolysis of 3- O -Glc of Rb3 was higher than that of 20- O -Xyl. Average mole yield: 48.2% C-Mx from Rb3, C-Mx1; 41.2% C-K from other ginsenosides. Abstract: The minor ginsensoides C-Mx, C-K were obtained from notoginseng leaf ginsenosides (mainly containing Rb3, C-Mx1, Rc, and Rb2) using special ginsenosidase type-I from Aspergillus niger g.848 strain. The enzyme molecular weight is about 75 kDa. The enzyme first hydrolyzed the C-20 position 20- O -Glc of ginsenoside Rb1, and then C-3 position 3- O -Glc via a single pathway: Rb1 → Rd → F2 → C-K. However, it first hydrolyzed 3- O -Glc of ginsenoside Rb2 and Rc, and then 20- O -Ara via a single pathway: Rb2→C-O → C-Y → C-K and Rc → C-Mc1 → C-Mc → C-K. It mainly hydrolyzed 3- O -Glc of Rb3 via pathway Rb3 → C-Mx1 → C-Mx → C-K, and slowly hydrolyzed 20- O -Xly of Rb3 via pathway Rb3 → Rd → F2 → C-K. The enzyme kinetic parameters Km and V max were 16.6 mM and 79.6 mM/h for Rb1; 20.4 mM and 45.6 mM/h for Rb2; 15.1 mM and 1.62 mM/h for Rb3 to Rd; 15.1 mM and 10.8 mM/h for Rb3 to C-Mx1; and 5.46 mM and 6.16 mM/h for Rc. To obtain minor ginsenoside by a low-cost method, the crude enzyme was made to react with 3% of notoginseng-leaf-ginsenosides at 45 °C and pH 5.0 for 48 h, and the resulting product was separated with a silica gel column; the average mole yields were 48.2% for C-Mx from Rb3 and C-Mx1, and 41.2% for C-K from other ginsenosides.